PENERAPAN MEDIA PEMBELAJARAN FILM DAN MODEL PEMBELAJARAN MAKE A MATCH DALAM MENINGKATKAN HASIL BELAJAR IPS SEJARAH - Wa Ima (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article focuses on a study that describes how the use of Film as learning media and Make A Match as learning models to improve the students’ learning outcomes in history’s social science learning subjects. The study was conducted at SMP Negeri 6 Leihitu Satap Kalauli for the sixth-grade students in the odd semester in the history’s social sciences learning subjects. Type of the study used classroom action research and the instruments used in the study were observation, interviews, and cognitive skill tests. Based on the analysis data, it was found that the students have an improvement in mastering the Indonesian history learning subjects of Masa Praaksara. Based on the analysis results, the researchers obtained the conclusion that the students' history social science learning subject outcomes increased before the preliminary test. Hence, the students achieved 75 as a score of 8 students. Nevertheless, after the action test in cycle 1 was conducted, 15 students achieved a score of 75 even though there was an improvement, but it was not based on the indicators of success, so the test was continued in the second cycle. After the second cycle was held, the test results were achieved that 21 people of 25 students could be categorized to be a success. It means that the results had achieved the indicator of success based on the researchers’ expectations and had achieved KKM.